REFLECTION OF BANARAS IN THE PAINTINGS OF JAYASRI BURMAN - Saha, Neha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Banaras is a holy and spiritual city that attracts people from all over the country even writers and artists. Many artists captured the beauty of Banaras in their art. Jayasi Burman is one of those artists whose paintings offer a glimpse into the soul of Banaras. Her art captures the essence of the city’s rich traditions, its vibrant colors, and its spiritual fervor. She is known for her Indian mythological paintings. But when the author met her for research work, realized that she has a very close attachment to Banaras. Banaras always attracts her. The spirituality of the city and the faith of the people inspire her. Banaras, Vishwanath Goli, Kashi ghat, Jalyatra, etc. are the examples of Jayasri Burman’s paintings where we can see the impact of Banaras, its culture, and mythology. This paper will explore the works of Jayasri Burman and delve deep into the world of Banaras. We will go through the cultural legacy of the city and experience its mysterious charm through the eyes of this renowned artist, from the ghats of the river Ganges to the alleys of the old city.